Profiles of Adolescent Identity at the Intersection of Ethnic/Racial Identity, American Identity, and Subjective Social Status - Cheon, Yuen Mi; Ip, Pak See; Haskin, Milou; Yip, Tiffany (Frontiers in Psychology, 2020)
Ethnic/racial minority adolescents face the task of forming an identity in relation to their ethnic/racial group as well as to American society, while also developing awareness of their social status relative to salient social groups. Whereas previous studies have investigated individual social identity dimensions or examined how objective measures of ethnicity/race and socioeconomic status intersect, studies that take a holistic and person-centered approach to considering various configurations of multiple social identities with subjective measures have been less common. The current study addresses these gaps and explores profiles of ethnic/racial identity, American identity, and subjective social status among ethnic/racial minority adolescents. Next, differences in discrimination experiences, mental health and academic outcomes across these profiles were examined. Three distinct identity profiles emerged from the data —“weakly identified,” “high ethnic/racial identity moderate American identity,” and “moderate ethnic/racial identity and American identity.” The “weakly identified” demonstrated the highest levels of past discrimination experiences and depressive symptoms, while the “moderate ethnic/racial identity and American identity” group reported the lowest levels of school engagement. Interpretation of the profiles and associated outcomes and implications are discussed.